Poetic Devices and Rubrics on Luisa Gluck “An Adventure” - Sihite, Jubilezer; Simandalahi, Sabam Taruna (CV. Ridwan Publisher, 2021)
Poetry has a mystery contained in the choice of words a magical touch that can make the reader lulled. Through structures, certain issues can be addressed in a deeper analysis. The researcher focuses on the poetic device of Luisa Gluck's poetry